Differential effect of anesthetics on mucociliary clearance in vivo in mice - Feldman, Kyle S. (Sci Rep, 2021)
Respiratory mucociliary clearance (MCC) is a key defense mechanism that functions to entrap and transport inhaled pollutants, particulates, and pathogens away from the lungs. Previous work has identified a number of anesthetics to have cilia depressive effects in vitro. Wild-type C57BL/6 J mice received intra-tracheal installation of (99m)Tc-Sulfur colloid, and were imaged using a dual-modality SPECT/CT system at 0 and 6 h to measure baseline MCC (n = 8). Mice were challenged for one hour with inhalational 1.5% isoflurane, or intraperitoneal ketamine (100 mg/kg)/xylazine (20 mg/kg), ketamine (0.5 mg/kg)/dexmedetomidine (50 mg/kg), fentanyl (0.2 mg/kg)/1.5% isoflurane, propofol (120 mg/Kg), or fentanyl/midazolam/dexmedetomidine (0.025 mg/kg/2.5 mg/kg/0.25 mg/kg) prior to MCC assessment. The baseline MCC was 6.4%, and was significantly reduced to 3.7% (p = 0.04) and 3.0% (p = 0.01) by ketamine/xylazine and ketamine/dexmedetomidine challenge respectively. Importantly, combinations of drugs containing fentanyl, and propofol in isolation did not significantly depress MCC. Although no change in cilia length or percent ciliation was expected, we tried to correlate ex-vivo tracheal cilia ciliary beat frequency and cilia-generated flow velocities with MCC and found no correlation. Our results indicate that anesthetics containing ketamine (ketamine/xylazine and ketamine/dexmedetomidine) significantly depress MCC, while combinations containing fentanyl (fentanyl/isoflurane, fentanyl/midazolam/dexmedetomidine) and propofol do not. Our method for assessing MCC is reproducible and has utility for studying the effects of other drug combinations.